Occult Hepatitis B infection (OBI) in Indonesia: A Systematic Review - Muhammadiy, Noer Sidqi; Senjarini, Kartika; Fajrin, Fifteen Aprila; Velavan, Thirumalaisamy P.; My, Truong Nhat; Song, Le Huu (Faculty of Medicine, Universitas Jember, 2025)
Hepatitis B Virus (HBV) infection remains a significant global health concern, with various genotypes exhibiting distinct clinical characteristics. Occult hepatitis B infection (OBI) is a latent form of HBV infection that is difficult to detect and poses a risk of transmission, particularly among high-risk populations such as blood donors, hemodialysis patients, and kidney transplant recipients. In Indonesia, studies on HBV genotype diversity and OBI prevalence remain limited, highlighting the need for a systematic analysis better to understand genotype distribution and its implications for public health. This systematic review was conducted using the PRISMA guidelines. Literature searches were performed on Google Scholar, Springer, ResearchGate, ScienceDirect, and PubMed using keywords related to OBI, HBV genotypes, and the Indonesian population. Studies that met the inclusion criteria were analyzed to assess genotype distribution and OBI prevalence. Among 352 screened articles, 35 studies met inclusion criteria. Genotypes B and C were identified as predominant HBV strains, with regional distribution variations. The highest OBI prevalence was recorded in eastern Indonesia (13.03%), followed by central (4.31%) and western (3.36%) regions. Nested PCR was the primary detection method for OBI. The predominance of genotype C in eastern Indonesia may contribute to higher OBI prevalence, emphasizing the need for region-specific diagnostic and management strategies. Further research is necessary to elucidate the association between HBV genotypes and clinical outcomes in OBI patients.